Gambaran Tingkat Pengetahuan Ibu Tentang Pemberian Makanan Tambahan Pada Bayi Usia 0-6 Bulan Di Wilayah Puskesmas Karang Bintang Kabupaten Tanah Bumbu Tahun 2013 - Mahpolah Mahpolah; Nina Rahmadiliyani; Tri Astuti; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2015)
Background, achieve optimal growth and development, in the Global Strategy for Infant and Young Child Feeding, WHO / UNICEF recommend four important things to do, those are, first giving breast milk to the infant immediately within 30 minutes after the baby has born and then exclusive breastfeeding from birth until 6 months old infant, the third is supplement feeding (MP-ASI) since infants aged 6 months to 24 months besides breastfeeding, and continue breastfeeding until 24 months or more. Fact, there are still many mothers who are not breastfeed their babies exclusively, more than 50% infants in Indonesia have got extra food prematurely. The purpose of this study is to describe the level of mother’s knowledge about feeding in 0-6 months old infants. This is a descriptive study. Research sites in the Karang Bintang Public Health Centre, the sample study were mothers with babies 0-6 months ie 55 people. With the sampling method is Accidental sampling. Results showed that mother's knowledge of supplement feeding in infants aged 0-6 months in the Work Area of Karang Bintang Public Health Center in 2013 is just a few mothers who have good knowledge of infant feeding, which is 11 mothers (20.0%), while enough knowledge is 19 mothers (34.5%) and a less knowledge only 25 mothers (45.5%).